Supply–demand price decoupling in European-type day-ahead electricity markets - Anita Varga; Botond Feczkó; Marianna E.-Nagy; Dávid Csercsik (International Journal of Electrical Power & Energy Systems)
In this paper, we consider the possibility of supply–demand price decoupling in European-type day-ahead electricity markets, considering also the possibility of the supply price exceeding the demand price for some periods. Using a simple market model and an illustrative example, we show that this approach can resolve the paradoxical rejection of block orders and thus potentially increase the total social welfare and surplus of bidders. However, it has additional implications, which must be considered in a potential application. The first is the non-uniqueness of the decoupled market-clearing prices, while the second is that price decoupling affects the relation between the sum of individual bid surpluses and the total social welfare, as these values may no longer be equal, and the approach may imply a nonzero income for the auctioneer. To tackle the issue of non-uniqueness of market-clearing prices, we propose an iterative three-step clearing method. In the second part of the paper, we consider realistic-sized examples, analyze how the proposed approach affects the market outcome. We show that the proposed method reduces the number of paradoxically rejected block bids by 34%–42% and slightly increases the total welfare. In addition, we define a measure (opportunity cost of paradox rejection) to characterize the level of paradox rejection in a clearing solution. We show that the proposed price decoupling-based clearing method may significantly (34%–44%) decrease the value of this measure compared to the conventional clearing approach. We also study the computational demand of the proposed method.